PLA2G6-Associated Neurodegeneration (PLAN): Review of Clinical Phenotypes and Genotypes - Guo, Yu-pei; Tang, Bei-sha; Guo, Ji-feng (Frontiers in Neurology, 2018)
PLA2G6-associated neurodegeneration(PLAN) includes a series neurodegenerative diseases which result from the mutations in PLA2G6. PLAN has genetic and clinical heterogeneity, with different mutation sites, mutation types and ethnicities, and its clinical phenotype is different. The clinical phenotypes and genotypes of PLAN are closely intertwined and varying widely. Phospholipase A2 group VI gene(PLA2G6), encodes a group of VIA calcium-independent phospholipase A2 proteins(iPLA2β) which are enzymes involved in lipid metabolism. According to the onset age and progressive clinical features, PLAN can be classified into some subtypes: infantile neuroaxonal dystrophy(INAD), atypical neuroaxonal dystrophy(ANAD), and diseases performing as parkinsonian symdrom in which containing adult onset dystonia-parkinsonism(DP), autosomal recessive early-onset parkinsonism(AREP). In this review, we present an overview of PLA2G6-associated neurodegeneration in the context of current research.